2022
DOI: 10.29390/cjrt-2022-015
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and follow-up for children intubated in an adult-based community hospital system: A retrospective chart review

Abstract: Objectives Emergency intubation is a high-risk procedure in children. Studies describing intubation practices in locations other than pediatric centres are scarce and varied. This study described pediatric intubations in adult-based community emergency departments (EDs) and determined what factors were associated with intubated-related adverse events (AEs) and described outcomes of children transferred to a quaternary care pediatric institution. Methods This is a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In the present study, we also demonstrated a significant improvement in V˙O 2 at VT1, maximal workload, and duration of physical exercise which could potentially improve the QOL of patients with HFrEF and CKD. Improvement in QOL after CR has been widely demonstrated in various cardiac conditions including HF,9,11,47 or with comorbidities 48,49. The benefits of exercise on QOL are also well demonstrated in patients with CKD 26,44,45.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, we also demonstrated a significant improvement in V˙O 2 at VT1, maximal workload, and duration of physical exercise which could potentially improve the QOL of patients with HFrEF and CKD. Improvement in QOL after CR has been widely demonstrated in various cardiac conditions including HF,9,11,47 or with comorbidities 48,49. The benefits of exercise on QOL are also well demonstrated in patients with CKD 26,44,45.…”
Section: Discussionmentioning
confidence: 98%
“…Improvement in QOL after CR has been widely demonstrated in various cardiac conditions including HF, 9,11,47 or with comorbidities. 48,49 The benefits of exercise on QOL are also well demonstrated in patients with CKD. 26,44,45 However, to the best of our knowledge, no study has evaluated the benefits of CR on QOL in patients with CRS.…”
Section: Discussionmentioning
confidence: 99%